Pelatihan Membuat Video Pembelajaran Berbasis Technological Pedagogical Content Knowledge (TPACK) Terintegrasi Nilai-Nilai Islam - Ahsani, Eva Luthfi Fakhru; Raharjo, Ratih Listya (At Ta'dzim: Journal of Community Development, 2024)
This training is a Community Service with the aim of providing understanding and skills to educators in creating learning videos that are not only effective in terms of technology and pedagogy, but are also able to convey Islamic values. This training method is carried out by delivering material in the form of seminars and practices. The Community Service was carried out at MI 1 Matholibul Ulum. MI 1 Matholibul Ulum is located in Lebak Village, Pakis Aji District, Jepara Regency. The subjects in this research were MI 1 Matholibul Ulum teachers. The results of this service show that training in making learning videos based on Technological, Pedagogical and Content Knowledge (TPACK) can increase teacher skills. It is hoped that this training can be a way out to support the process of increasing teacher competency, in this case technological capabilities in learning.